Rastreamento de abusos e maus-tratos contra indivíduos idosos residentes em instituições de longa permanência - Hasten-Reiter Júnior, Hermann Nogueira (2013)
Objective: Screen abuse and mistreatment in elderly residents in long-stay institutions and correlate the results obtained in the elderly and caregivers in two LSIs. Methods: Observational study conducted in the city of Maceió, Alagoas, Brazil, with seniors and caregivers, linked to two major long-stay institutions (A and B) located in that municipality. The sample consisted of 94 individuals, with 81 seniors and 13 caregivers. Data collection was conducted through instruments applied in the form of interviews and physical examinations. For the socio-economic and demographic assessment and abuse and mistreatment screening in the elderly used the questionnaire Instrumento de Rastreamento de Abuso e Maus-Tratos em Idosos - IRAMI and evaluation of caregivers was used to cross-cultural adaptation of the Caregiver Abuse Screen - CASE and analyzed with the software SPSS 15.0. This study research project was approved by the Ethics and Research committee of the Federal University of Alagoas under protocol number 013032-2010-04. Results: Among the elderly, there was a predominance of females, with a mean age of 77.3 years old, unmarried and in length of stay between 01 to 10 years. Among the morbidities was statistic significance in cases of high blood pressure and coronary heart disease. Among the signs of abuse and mistreatment, there were significant between careless dress, falls and regular use of medications, these statistical differences express realities of life and morbidity, which may be related to the care and related factors such as environmental conditions offered by the institution . Conclusion: The findings of this research show that the signs of abuse found warn of increased attention to the institutionalized elderly.